IMPACT OF ELECTRIC CURRENT ON SMAW WELDING STRENGTH - Abdul Rahman Agung Ramadhan; Abdul Muchlis; Fadila Muhammad Hidayat (International Journal Science and Technology, 2023)
Welding Shield Metal Arc Welding is a process of joining two metals by utilizing heat from jumping electrodes at two different poles. In this welding technique, the connecting material or metal material (electrode) is metal that has been coated with flux (welding slag). This study aims to determine whether current variations affect the impact strength in the SMAW welding process. In this study, welding was carried out on the ST 41 material using the E 6013 electrode with electric current variants on the SMAW welding machine, namely: 60 A and 85 A, followed by the Charphy impact test used to determine the strength of the ST 41 steel connection. The results obtained with the ST41 200A material were 0.566 J/mm2 and for the ST41 210A material, it was obtained 1.662 J/mm2. With research showing that the greater the amperage, the greater the effort required in the Charphy impact test and the greater the amperage, the greater the value of the Charphy impact test.